PENGEMBANGAN ONLINE PUBLIC ACCESS CATALOG (OPAC) BERBASIS ANDROID PADA PERPUSTAKAAN UPN â€œVETERANâ€ JAKARTA - Nugroho, Fajar; Muljono, Pudji; Hermadi, Irman (Edulib, 2017)
Abstract. UPN "Veteran" Jakarta Library wants to keep abreast of information technology development that can improve library quality. Smartphone with android operating system nowadays is one of knowing information technology that developed rapidly. The advantages of smartphones using android operating system is the ability to run multiple applications simultaneously, ease of access, and has a relatively cheap price with a lot of functions. The UPN "Veteran" JakartaLibrary currently has limitations in providing a collection search facility due to the less roomy space, the cost of electricity, and also the ergonomics of the device. Online Public Access Catalog (OPAC) or that can be known byonline catalog is a useful facility for the user and library in providing the means. Development OPAC withandroid-basedis expected to provide solutions to problems that can help users and also UPN "Veteran" JakartaLibrary in providing excellent service. In this research article will be presented about the stages of OPAC with android-bases development in UPN "Veteran" Jakarta Library by using System Development Life Cyle (SDLC) method. From the result of the research, it is concluded that thedevelopment of OPAC with android-bases in UPN "Veteran" Jakarta Library has been able to provide ten parameters of OPAC third generation. With the android-based OPAC is expected to help the user infinding the collection with the limitations of the search facilities provided by UPN "Veteran" Jakarta as well as providing variations in searching collection at OPAC library UPN "Veteran" Jakarta.Keywords: Development, OPAC, Android